Changes in Prosocial Motivation over Time: A Cross-Sector Analysis of Effects on Volunteering and Work Behavior. Issue 14 (26th October 2018) - Kroll, Alexander; Vogel, Dominik
ABSTRACT: A gap in research on prosocial motivation is that very little is known about its change across time, let alone, how such changes affect employee behavior. Using multiple waves of panel data, covering a period of sixteen years, this article finds that prosocial motivation is mostly stable, and there are no broader socialization effects in the private and public sector. However, when prosocial motivation increases, it leads to increases in either work or volunteering behavior, suggesting that public employees may use alternative outlets to realize their motivation if such motivational capital cannot be linked to the mission of their organizations.